2014
DOI: 10.1155/2014/710602
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Subjective Social Status with Physical Activity and Body Mass Index across Four Asian Countries

Abstract: Objective. The aims of this study were to (1) assess physical activity and weight status differences and (2) explore the direction and shape of subjective social status (SSS) association with physical activity and weight status within four Asian countries. Methods. Cross section data of adult respondents from the nationally representative East Asian Social Survey were used for analyses. Logistic regression stratified by gender was conducted for the first aim, and simple and quadratic logistic regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 53 publications
2
12
1
Order By: Relevance
“…One area of deficiency was in study samples being insufficiently representative of the target population due to the use of convenience samples, 24 26 lack of description of recruitment strategies, 21 25 lack of reporting of response rates, 17 25–27 high or unreported exclusion rates 23–26 and lack of reporting of participant demographics. 19 22 In addition, nearly three-quarters of included studies only performed limited adjustment of non-SES confounders, such as for age alone, or age and marital status, without consideration of comorbidities or cardiovascular risk behaviours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One area of deficiency was in study samples being insufficiently representative of the target population due to the use of convenience samples, 24 26 lack of description of recruitment strategies, 21 25 lack of reporting of response rates, 17 25–27 high or unreported exclusion rates 23–26 and lack of reporting of participant demographics. 19 22 In addition, nearly three-quarters of included studies only performed limited adjustment of non-SES confounders, such as for age alone, or age and marital status, without consideration of comorbidities or cardiovascular risk behaviours.…”
Section: Resultsmentioning
confidence: 99%
“…Because a majority of studies presented stratified ORs without an overall summary measure, 17 19–24 and because studies used different comparison groups (with some reporting ORs between the bottom vs the top of the SSS ladder, 19 22 others reporting ORs per 1, 20 25 26 1.6 27 or 2 23 24 rung increases in SSS, and still others, per quartile change in SSS 17 21 ) we calculated a single weighted-effect estimate comparing the bottom (lowest rung) with the top (highest rung) of the SSS ladder to facilitate comparisons across studies. This was achieved through the following steps: (1) if both community and societal ladders were used to measure SSS, only ORs for societal ladders were considered; (2) if multiple effect estimates for a single outcome were reported in a single study, the OR using the broadest level of comparison was used; (3) reciprocals of all ORs that used lower SSS as the reference group were taken, so that higher SSS became the reference group; (4) all ORs were converted to logs (ORs); (5) each stratified log (OR) was multiplied by the proportion of the sample in that stratum, then summed across strata, resulting in one weighted log (OR) per outcome per study; (6) weighted logs (ORs) were calculated comparing the bottom rung with the top rung of the SSS ladder, then converted back to ORs.…”
Section: Methodsmentioning
confidence: 99%
“…More young adults in LMICs of South-East Asia (51%) and South Asia and China (46%) had insufficient PA than those in LMICs in Near East and Central Asia (32%), and sub-Saharan Africa (37%) (Pengpid et al 2015). Other studies with Asian young adults have also reported a high prevalence of insufficient PA: 41% to 49% in Malaysia (Mohammed et al 2014;Sreeramareddy et al 2012) and 71% in China (Frerichs et al 2014). Among young adults in South Asia, those in Pakistan were found to have the highest prevalence of insufficient PA (81%) while those in India had the lowest prevalence of insufficient PA (25%) (Pengpid et al 2015).…”
Section: Activity Behaviours In Young Adults In Low-and Middle-incomementioning
confidence: 92%
“…Available evidence, mostly from university students, suggests that the prevalence of physical inactivity in young adults in low-and middle-income countries is higher (44%) than in highincome countries (39%) (Pengpid et al 2015). The few studies in Asian countries have reported the prevalence of inactivity among young adults to be 41% in Malaysia (Mohammed et al 2014), 50% in Taiwan, 52% in South Korea, 71% in China and 75% in Japan (Frerichs et al 2014). Although some physical activity data for Bangladesh are available for adults aged ≥25 years (Mohan et al 2016;Pengpid et al 2015), no data are available for young adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation